Superalloy 718 and Derivatives 2010
DOI: 10.1002/9781118495223.ch51
|View full text |Cite
|
Sign up to set email alerts
|

Modeling and Simulation of Alloy 718 Microstructure and Mechanical Properties

Abstract: Alloy 718 is a unique superalloy that has been in use for a number of years. It also has the distinction to be utilized throughout the aerospace and general industrial communities. The applications for this material are often very unique and require tailoring of the microstructure and subsequently the mechanical properties to meet these specific needs. To support optimization of Alloy 718 mechanical properties and performance, considerable work has been conducted by the materials community to develop materials… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…Computational modeling and simulation has been applied to various material and processing aspects of Alloy 718. [3] Focused efforts to establish through-process modeling capabilities have resulted in modeling tools and demonstration efforts for Alloy 718 turbine engine rotor design and fabrication. [8] More recent efforts have focused on machining distortion due to residual stresses.…”
Section: Advances In Modeling and Simulation Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Computational modeling and simulation has been applied to various material and processing aspects of Alloy 718. [3] Focused efforts to establish through-process modeling capabilities have resulted in modeling tools and demonstration efforts for Alloy 718 turbine engine rotor design and fabrication. [8] More recent efforts have focused on machining distortion due to residual stresses.…”
Section: Advances In Modeling and Simulation Methodsmentioning
confidence: 99%
“…Models that support atomistic simulation through continuum process modeling are now being used to further advance Alloy 718 for unique capabilities, improved process efficiency and reduced costs. [3] Alloy 718 has been applied to many industrial applications. [4] The features that have made Alloy 718 so attractive include: relatively low cost as compared to more highly alloyed superalloys, ease in manufacturing, and the ability to tailor the microstructure and properties for specific applications.…”
Section: Introductionmentioning
confidence: 99%
“…As noted earlier relative to DA718, computational materials modeling has become enabling to achieve the desired microstructure and subsequent mechanical properties on a component location-specific basis. [16,17] In addition to microstructure and mechanical property models, additional modeling and simulation capabilities have been established to support existing and emerging manufacturing processes. Machining modeling has advanced to the point where optimal machining parameters can be designed computationally to enable desired component configuration and surface characteristics to be demonstrated the first time in actual production.…”
Section: Advances In Alloy 718 Technologymentioning
confidence: 99%
“…Dynamic and post-dynamic recrystallization is among the most important phenomena impacting the microstructure of hot-forged components. The influence of the thermomechanical forging conditions on dynamic recrystallization (DRX) kinetics and on the DRX grain size is relatively well established [1][2][3][4][5][6][7][8], and can even be predicted using either physical or empirical models [9][10][11][12][13][14][15]. However, previous studies have shown that post-dynamic evolutions may also considerably impact the final microstructure [12,[15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%